Small Bowel Obstruction with Perforation Secondary to PillCam - Toan Pham; Ashley Miller; Domenic La Paglia; Alvin Cham (Case Reports in Gastrointestinal Medicine)
We present a case of a 63-year-old female who presented with small bowel obstruction and perforation secondary to a retained PillCam®. She initially presented with iron-deficiency anaemia (haemoglobin 44 g/L, ferritin 190 mcg/L). After unremarkable upper and lower gastrointestinal endoscopies and biopsies, she was referred for wireless capsule endoscopy (WCE). Four days afterwards she re-presented with small bowel obstruction and perforation related to the PillCam, which was confirmed on X-ray, on computed topography (CT), and at laparotomy.